Horribly Wrong - Bush, Stephen S. (Journal of religious ethics, 2013)
Moral horror is an extreme emotional response to that which violates things we regard as sacred. In Robert Merrihew Adams's view, horror is a response to badness and not to wrongness, and so one could properly regard some actions as horrible but not wrong. In contrast, I argue that horror, when directed toward actions, is only appropriate for wrong actions. The reason is that horror involves moral disgust, and agents who committed a horrible action would have self-disgust, that is, they would be repulsive to themselves. I argue, with reference to killing in combat and in self-defense, that those who have done no wrong should not be in such a state.